Multiple description coding for enhancing outage and video performance over relay-assisted cognitive radio networks - Ibrahim, N. K.; Sali, A.; A. Karim, H.; Ramli, A. F.; Ibrahim, N. S.; Grace, D. (Institute of Electrical and Electronics Engineers, 2022)
Multimedia content delivery, such as video transmission over wireless networks, imposes significant challenges include spectrum capacity and packet losses. The cognitive radio (CR) technology is developed to solve the spectrum issue, while multiple description coding (MDC) is one of the promising source coding techniques to alleviate packet loss problems and exploit the benefit of path diversity. The source information was split into several descriptions in MDC, then transmitted over a network with multiple paths. The quality of the received data increases with the number of descriptions received at the receiver. In this paper, the proposed system comprises of relay-assisted cognitive radio network using the MDC technique for video transmission. In the simulations, the outage performance of the MDC scheme over two networks, which were relay-assisted network and non-relay network, were compared. Then, the outage probability was used to estimate the video quality, peak signal to noise ratio (PSNR) of the received video. The results obtained show the benefits of the relay assisted networks by 9% improvement on average outage performance over the non-relay network. Furthermore, the video performance improved by an average of 9% in PSNR compared to the non-relay system.